Peningkatan Minat dan Budaya Membaca Melalui Pelatihan Pengelolaan Perpustakaan Keluarga - Indah Kurnianingsih; Rosini Rosini; Sri Chusri; Wardiyono Wardiyono (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
One of the ways to internalize reading interest in the family is to have a book or resource collection at home designated to the needs of each family's member. These books collection need to be managed as a home library to fulfill the purpose as a source of information for the family. By managing this library, the collection can also be retrieved easily. The scope material in this engagement includes strategies to increase reading interest in the family, introducing new ideas of the design concept, and the use of home library space, practices in managing and maintaining the collection, and demo of SLiMS open source application utilization for home library. The evaluation results of the engagement showed that 83.8 percent of participant scored at average value in the test of a simple classification for library collection is. There are 5 participants get the score of 100. 72% of participants indicate the desire and concern to organize and to create a comfortable and attractive home library. 95% of participants valued the training provided as usefull and 98% of participants answered the training material is relevant to the needs of the participants. Furhter more, this Training of Family Library Management for Member of Dharma Wanita Finance Ministry Republic Indonesia can be applied by various elements of society as part of the strategies in developing awareness of the national spirit literacy movement from the family.